Listening With Courtesy: A Conversation with Tim Lilburn - Whetter, Darryl (Studies in Canadian Literature, 1997)
Tim Lilburn does not think of himself as a writer, but as someone who looks, or someone who engages in various contemplative acts. He uses essays to figure things out, to draw lines from one point to another, something the poem can't do, or would do quite awkwardly. Poetry, however, is necessary to the human condition, because without poetic attention, the world could become too clear, and this is dangerous. His most recent book, Moosewood Sandhills is full of imperatives and references to "necessity". Poetry is a "courteous" way of seeing, but for Lilburn, all writing is truth-telling, a response to the oddness and distance of things.